Chalcone-based carbamates for Alzheimer's disease treatment. (May 2017) - Rampa, Angela; Montanari, Serena; Pruccoli, Letizia; Bartolini, Manuela; Falchi, Federico; Feoli, Alessandra; Cavalli, Andrea; Belluti, Federica; Gobbi, Silvia; Tarozzi, Andrea; Bisi, Alessandra
Aim: Alzheimer's disease is a still untreatable multifaceted pathology, and drugs able to stop or reverse its progression are urgently needed. In this picture, the recent reformulation of the cholinergic hypothesis renewed the interest for acetylcholinesterase inhibitors. In this paper, a series of naturally inspired chalcone-based carbamates was designed to target cholinesterase enzymes and possibly generate fragments endowed with neuroprotective activity in situ .Results & methodology: All compounds presented in this study showed nanomolar potency for cholinesterase inhibition. Notably, fragment11d also displayed an interesting neuroprotective profile.Conclusion: These new derivatives are able to simultaneously modulate different key targets involved in Alzheimer's disease, and could be regarded as promising starting points for the development of disease-modifying drug candidates.